Dynamic expression of Lgr6 in the developing and mature mouse cochlea - Zhang, Yanping; Chen, Yan; Ni, Wenli; Guo, Luo; Lu, Xiaoling; Liu, Liman; Li, Wen; Sun, Shan; Wang, Lei; Li, Huawei (Frontiers in Cellular Neuroscience, 2015)
The Wnt/β-catenin signaling pathway plays important roles in mammalian inner ear development. Lgr5, one of the downstream target genes of the Wnt/β-catenin signaling pathway, has been reported to be a marker for inner ear hair cell progenitors. Lgr6 shares approximately 50% sequence homology with Lgr5 and has been identified as a stem cell marker in several organs. However, the detailed expression profiles of Lgr6 have not yet been investigated in the mouse inner ear. Here, we first used Lgr6-EGFP-Ires-CreERT2 mice to examine the spatiotemporal expression of Lgr6 protein in the cochlear duct during embryonic and postnatal development. Lgr6-EGFP was first observed in one row of prosensory cells in the middle and basal turn at embryonic day 15.5 (E15.5). From E18.5 to postnatal day 3 (P3), the expression of Lgr6-EGFP was restricted to the inner pillar cells (IPCs). From P7 to P15, the Lgr6-EGFP expression level gradually decreased in the IPCs and gradually increased in the inner border cells (IBCs). At P20, Lgr6-EGFP was only expressed in the IBCs, and by P30 Lgr6-EGFP expression had completely disappeared. Next, we demonstrated that Wnt/β-catenin signaling is required to maintain the Lgr6-EGFP expression in vitro. Finally, we demonstrated that the Lgr6-EGFP-positive cells isolated by flow cytometry could differentiate into myosin 7a-positive hair cells after 10 days in-culture, and this suggests that the Lgr6-positive cells might serve as the hair cell progenitor cells in the cochlea.